THE IMPLEMENTATION OF ARABIC LANGUAGE LEARNING IN THE TOURIST TRAVEL BUSINESS STUDY PROGRAM: PELAKSANAAN PEMBELAJARAN BAHASA ARAB DI PROGRAM STUDI USAHA PERJALANAN WISATA - ernawati, euis (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This research seeks to reveal the phenomena that occur in learning Arabic in the Travel Business study program. The purpose of this study was to determine Arabic learning activities, learning components related to Arabic courses, and student responses to learning Arabic in the Travel Business study program. The method used in research is descriptive method with a qualitative approach. The subjects in this study were the study program heads, Arabic language lecturers, and fourth semester students in the travel business study program. Collecting data in this study was in the form of observation, interviews, and documentation studies as data triangulation. Based on the research results, it is known that the implementation of learning Arabic in the study program has been going well. Learning consists of initial, core, and closing activities. Existing facilities are complete and can support the learning process, lecturers have a linear educational background with the subjects taught and have good competence, lecturers teach using various methods and learning media, and the teaching materials used are books written by the lecturer concerned, adjusts to the existing curriculum and RPS. In addition, student responses to learning Arabic were also good even though it was the first time learning Arabic. The form of evaluation given tends to be in the form of oral because they are required to be more active in speaking than just theory. Keywords: Implementation of learning, Arabic Language, Travel Business Study Program